Glioma-Associated Stromal Cells Stimulate Glioma Malignancy by Regulating the Tumor Immune Microenvironment - Cai, Xiangming; Yuan, Feng; Zhu, Junhao; Yang, Jin; Tang, Chao; Cong, Zixiang; Ma, Chiyuan (Frontiers in Oncology, 2021)
Background The glioma-associated stromal cell (GASC) is a recently identified type of cell in the glioma microenvironment and may be a prognostic marker for glioma. However, the potential mechanisms of GASCs in the glioma microenvironment remain largely unknown. In this work, we aimed to explore the mechanisms of GASCs in gliomas, particularly in high-grade gliomas (HGG). Methods We used glioma datasets from The Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA). We utilized the Single-sample Gene Set Enrichment Analysis (ssGSEA) algorithm to discriminate between patients with high or low GASC composition. The xCELL and CIBERSORT algorithms were used to analyze the composition of stromal cells and immune cells. Risk score and a nomogram model were constructed for prognostic prediction of glioma. Results We observed for the first time that the levels of M2 macrophages and immune checkpoints (PD-1, PD-L1, PD-L2, TIM3, Galectin-9, CTLA-4, CD80, CD86, CD155, and CIITA) were significantly higher in the high GASC group and showed positive correlation with the GASC score in all glioma population and the HGG population. Copy number variations of DR3 and CIITA were higher in the high-GASC group. THY1, one of the GASC markers, exhibited lower methylation in the high GASC group. The constructed risk score was an independent predictor of glioma prognostics. Finally, a credible nomogram based on the risk score was established. Conclusions GASCs stimulate glioma malignancy through the M2 macrophage, and are associated with the level of immune checkpoints in the glioma microenvironment. The methylation of THY1 could be used as prognostic indicator and treatment target for glioma. However, further studies are required to verify these findings.